Environmental Disclosure and Efficiency Performance of Energy Company: Case Study of Indonesia - Kusmayadi, Dedi; Firmansyah, Irman (International Journal of Energy Economics and Policy, 2023)
This study aims to investigate the efficiency performance of energy companies, especially the environmental disclosure variable as the energy companies’ responsibility to the environment, especially in achieving the SDGs. In addition, several other factors were also tested to determine their effect on the level of efficiency. The study was conducted on 42 energy companies in Indonesia for the period 2018 to 2021. Efficiency analysis uses Data Envelopment Analysis with input and output variables from each financial report. Meanwhile, STATA software was used to analyze the regression. The results show that the efficiency level of gas and oil companies is more optimal than other companies. However, coal companies are better at predicting the level of efficiency. This is in line with the huge energy potential in Indonesia that comes from coal. Another finding is that although environmental disclosure has not succeeded in increasing efficiency performance, it can moderate the relationship between size and efficiency level.